2010
DOI: 10.1111/j.1365-2702.2010.03387.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among self‐esteem, job adjustment and service attitude amongst male nurses: a structural equation model

Abstract: In clinical practice and management, our findings provide concrete directions for nursing management and professionals in helping male nurses adjust to their job to improve male nurses' service attitude. More clinical situation must be provided and practiced before male nursing students graduate from school. We suggest future study is needed to generalise this model to different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
3
15
0
2
Order By: Relevance
“…34 The research of self-esteem is based on three theories. 34 The research of self-esteem is based on three theories.…”
Section: The Mediating Role Of Self-esteemmentioning
confidence: 99%
See 2 more Smart Citations
“…34 The research of self-esteem is based on three theories. 34 The research of self-esteem is based on three theories.…”
Section: The Mediating Role Of Self-esteemmentioning
confidence: 99%
“…34 Another study proposed that employees could be motivated by success achieved in the workplace, so that they were willing to stay in the current group. This study found that self-esteem was positively correlated with work productivity and sense of belonging to the organization.…”
Section: The Mediating Role Of Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…이러한 편견으로 인해 환자들은 남자간호사의 간호를 거부하며, 고용기관과 동료 의료인들도 남자간호사를 차별대 우하는 경향이 있다 (Chen, Fu, Li, Lou, & Yu, 2012a). 이와 같은 성 고정관념과 편견, 차별로 인해 남자간호사는 상처를 받고 성역할에 혼란을 겪고 있으며, 이는 직무만족 저하와 이 직으로 연계되고 있다 (Lou, Li, Yu, & Chen, 2011). 남자간 호사 이직율은 1년 내 23.6%, 5년 내 44.7%이며, 4년 내 이직 률은 여자간호사의 약 2배에 해당한다 (Chen, Yu, Hsu, Lin, & Lou, 2012b).…”
unclassified
“…Individual characteristics may play a role in how students integrate these attitudes. Types of programs and educational experiences, such as clinical placement in community versus academic institutions, may influence students' knowledge, skills, and attitudes (Sullivan, Hirst, & Cronenwett, 2009); having children or being a caregiver has been associated with more positive patient-centered attitudes (Johnson & Lindschau, 1996); and ethnicity and gender have been found to factor into professional values (Lou, Li, Yu, & Chen, 2011;Wros, Doutrich, & Ruiz, 2009).…”
mentioning
confidence: 99%